An Fe-doped NiV LDH ultrathin nanosheet as a highly efficient electrocatalyst for efficient water oxidation. Issue 7 (10th June 2019) - Wang, Zhaolong; Liu, Wenjun; Hu, Yiming; Xu, Li; Guan, Meili; Qiu, Jingxia; Huang, Yunpeng; Bao, Jian; Li, Huaming
Abstract : An Fe-doped NiV LDH ultrathin nanosheet was fabricated as a highly efficient electrocatalyst for efficient water oxidation. Abstract : Exploring highly efficient and low-cost electrocatalysts for water oxidation to meet industrial requirements is an ongoing challenge. In this work, we report a NiV LDH ultrathin nanosheet doped with Fe 3+ through a one-step co-precipitation method. Benefiting from the successful doping of Fe 3+, which could effectively enhance the oxidation capacity of Ni 3+ and facilitate the charge transport of NiV LDH, the ultrathin Ni3 V1 Fe1 LDH nanosheet shows an efficient catalytic performance for the water oxidation. A low overpotential of 269 mV was required achieving the current density of 10 mA cm −2 and a long-term stability for 1000 cycles was also shown for the obtained electrode. This work provides a facile pathway for preparing Ni-based LDH materials and makes them promising catalysts for the oxygen evolution reaction.